2022
DOI: 10.31351/vol31iss1pp154-166
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation the Effectiveness of Phenolic Compound of Salvia Frigida on Induced Atopic Dermatitis in Experimental Mice

Abstract: Abstract To evaluate the effectiveness of Phenolic Compound of Salvia Frigida on induced atopic dermatitis (AD) of mice. Forty mice were included in the study, divided in to four groups (10 mice/group): apparently healthy, induced AD without treatment, induced AD treated with tacrolimus 0.1% ointment, and induced AD treated with Phenolic Compound of Salvia Frigida cream 5%. Examination of histopathology was done and skin homogenates levels also measured. Levels of WBC, Eosinophil, skin tissue homogenate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…People suffering from psoriasis are more likely to have complications that are not limited to skin conditions. These encompass type 2 diabetes, obesity, coronary artery diseases, autoimmune diseases, and psychiatric issues. There is more evidence that psoriasis may arise simultaneously or consecutively with additional immune-mediated skin eruptions, most notably eczematous dermatitis. Research has also revealed links between psoriasis and an array of immune-associated conditions, among them ulcerated intestinal colitis. In addition, kidney impairment is known as one of the consequences of psoriasis. Moreover, arrays of drugs have been significantly implicated in the initiation and aggravation of psoriasis, namely, chloroquine, interferons, imiquimod, tetracyclines, and β-blocking agents …”
Section: Objective Of the Studymentioning
confidence: 99%
“…People suffering from psoriasis are more likely to have complications that are not limited to skin conditions. These encompass type 2 diabetes, obesity, coronary artery diseases, autoimmune diseases, and psychiatric issues. There is more evidence that psoriasis may arise simultaneously or consecutively with additional immune-mediated skin eruptions, most notably eczematous dermatitis. Research has also revealed links between psoriasis and an array of immune-associated conditions, among them ulcerated intestinal colitis. In addition, kidney impairment is known as one of the consequences of psoriasis. Moreover, arrays of drugs have been significantly implicated in the initiation and aggravation of psoriasis, namely, chloroquine, interferons, imiquimod, tetracyclines, and β-blocking agents …”
Section: Objective Of the Studymentioning
confidence: 99%
“…Br., and S. sclareoides Brot. reduced the enzymatic activity of elastase and inflammatory mediator molecules, such as nitric oxide (NO), IL-4, IL-13, IL-5, TNF-α, cyclooxygenase (COX)-2, and prostaglandine PGE2 in RAW 264.7 macrophages induced with LPS in organic extracts of different polarities and aqueous extracts [65][66][67][68][69][70]. The polar extracts of S. chudei Batt.…”
Section: Pharmacologymentioning
confidence: 99%
“…In the case of Salvia, terpenes of abietane, clerodane, labdane, and pimarane-type structures have been described. Some examples are tanshinone IIA (C14) and sclareol (C15) isolated from S. miltiorrhiza and S. sclarea, respectively [61][62][63][64][65][66][67][68][69][70][71]. In the case of the genus Isodon, compounds with a Kaurano-type skeleton predominated, and some common cases among the species were adenanthine (C16), eriocalyxin B (C17), and oridonine (C18) [114,117,169].…”
Section: Phytochemistrymentioning
confidence: 99%